Manhunter - De Laurentiis, Dino; Roth, Richard, 1943-; Williams, Bernie; Mann, Michael, 1943-; Petersen, William L., 1953-; Greist, Kim; Farina, Dennis, 1944-2013; Allen, Joan, 1956-; Cox, Brian, 1946-; Lang, Stephen, 1952-; Noonan, Tom; Rubini, Michael; et al. ([United States] : Metro-Goldwyn-Mayer ; Beverly Hills, CA : Distributed by Twentieth Century Fox Home Entertainment, 2007)
FBI agent Will Graham captured the diabolical Dr. Hannibal Lecter but nearly lost his mind in the process and retired from the Bureau. When he is coaxed out of retirement to hunt a serial killer called "The Tooth Fairy," he is again faced with the horrors incumbent in entering a serial killer's mind.
Based on the novel Red dragon by Thomas Harris.
DVD release of the 1986 motion picture.
Includes trailers.
Original music composed and performed by the Reds & Michel Rubini ; edited by Dov Hoenig ; production desinger, Mel Bourne ; director of photography, Dante Spinotti ; costume designer, Colleen Atwood.
William Petersen, Kim Greist, Dennis Farina, Joan Allen, Brian Cox, Stephen Lang, Tom Noonan.
MPAA rating: R.
Keywords: Lecter, Hannibal -- (Fictitious character), -- 1933- -- Drama; United States. -- Federal Bureau of Investigation -- Drama; Serial murderers -- United States -- Drama; Government investigators -- United States -- Drama; Feature films; Horror films; Thrillers (Motion pictures); Film adaptations; Fiction films; Video recordings for the hearing impaired